Efektivitas Diplomasi dan Komunikasi Strategis dalam Kampanye Melawan Terorisme di Indonesia - Talolo Muara; Hayatul Khairul Rahmat; Triyoga Budi Prasetyo (Jurnal Dinamika Sosial Budaya, 2021)
The purposes of this paper are to: (a) explore terminology of terrorism; (b) recognize the wave theory of terrorism; (c) describe the countermeasures of terror in Indonesia; (d) explore the effectiveness of diplomacy and strategic communication in the campaign against terrorism in Indonesia. The method used in this research is literature review with content analysis techniques. The findings of this study are (a) acts of terrorism can be carried out based on a logic of action or method of action; (b) Currently, Indonesia is in a religious wave so that in facing terrorism it uses a law enforcement approach; (c) In addition, Indonesia tends to use a soft approach, namely cooperation within UN organizations and the BNPT deradicalization program; and (d) Indonesian representatives in non-permanent members of the UN Security Council are a form of diplomacy and strategic communication which certainly plays a strategic role in dealing with terrorism, countermeasures against terrorism, and a commitment to reject the association of acts of terrorism with certain religions, ethnicities and/ or nations..